IMPLEMENTASI PELAYANAN RUMAH SEHAT LANSIA (RUSELA) SEBAGAI UPAYA MENINGKATKAN DERAJAT KESEHATAN LANSIA DI KOTA YOGYAKARTA - Nur Fitri Mutmainah (Yogyakarta State University, 2017)
This paper analyzes the implementation of the Rumah Sehat Lansia (RUSELA), a public service innovation for the high elderly population in Yogyakarta City. The high elderly population and Usia Harapan Hidup (UHH) in Yogyakarta City requires the government intervention due to elder's health record improvement to optimize public service for elderly related to their health. Qualitative descriptive approach was used to explain the research in an objective, detailed, and deep way. Observation, interview, and documentation were applied by the researcher to collect the data. The result shows that the implementation of RUSELA, seen from communication aspect, has been already good. Seen from the resource aspect, especially financial resource, RUSELA should be collaborated with others institutions, private sector, and public community to improve the service and facilities so that the program can be implemented successfully. Looked from disposition and structure bureaucracy aspect have been running well.Keywords: Implementation program, Health Care, RUSELA, and Yogyakarta City